2007
DOI: 10.1109/iembs.2007.4352392
|View full text |Cite
|
Sign up to set email alerts
|

A Preliminary Study on Driver's Stress Index Using a New Method Based on Differential Skin Temperature Measurement

Abstract: Prolonged periods of driving in monotonous situations may lower a driver's activation state as well as increasing their stress level due to the compulsion to maintain safe driving, which may result in an increased risk of a traffic accident. There is therefore an opportunity for technological assessment of driver physiological status to be applied in-car, hopefully reducing the incidence of potentially dangerous situations. As part of our long-term aim to develop such a system, we describe here the investigati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
25
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(29 citation statements)
references
References 6 publications
3
25
0
1
Order By: Relevance
“…Analysis of these indicators revealed some patterns. For instance, throughout the whole duration of driving task PST was monotonically decreasing (see Figure 4c); similar pattern was observed by Yamakoshi et al in [19]. In contrast, GSR did not counteract pattern observed in PST (see Figure 4a), but instead was found to strongly correlate to participants' subjective overall workload ratings.…”
Section: Discussionsupporting
confidence: 84%
“…Analysis of these indicators revealed some patterns. For instance, throughout the whole duration of driving task PST was monotonically decreasing (see Figure 4c); similar pattern was observed by Yamakoshi et al in [19]. In contrast, GSR did not counteract pattern observed in PST (see Figure 4a), but instead was found to strongly correlate to participants' subjective overall workload ratings.…”
Section: Discussionsupporting
confidence: 84%
“…Emotional excitement or apprehension is known to induce a slight increase in human skin temperature (Elam & Wallin, 1987;Oka et al, 2001Oka et al, , 2008Yamakoshi et al, 2007;Ziegler & Cash, 1938). Although several authors have demonstrated stress-induced skin temperature changes, the mechanisms by which odorants induce such changes are unknown.…”
Section: Discussionmentioning
confidence: 99%
“…If feelings of excitement or apprehension induce slight increases in skin temperature (Elam & Wallin, 1987;Oka et al, 2001Oka et al, , 2008Yamakoshi et al, 2007;Ziegler & Cash, 1938), it is reasonable to assume that essential oils can be regarded as having either distressing/agitating properties when associated with increases in skin temperature or relaxing/sedating properties when associated with decreases in skin temperature. Mehrabian and Russell (1974) constructed a set of verbal texts describing different situations, and a scale for rating these texts (the Semantic Differential Scale).…”
Section: Discussionmentioning
confidence: 99%
“…Conclusively, we found that multi-channel skin thermometer data might complement the statistical defects of the relevant sensory spectra. Emotional excitement or apprehension is known to induce a slight increase in skin temperature (Elam & Wallin, 1987;Oka et al, 2001Oka et al, , 2008Yamakoshi et al, 2007;Ziegler & Cash, 1938). As the perception of and response to odors are intimately related to both emotional expression and genesis of emotion, skin temperature changes can serve as an effective index for the study of the relationship between odor and its emotional and physiological responses in humans.…”
Section: Multi-channel Skin Thermometer Study: Assessing the Statistimentioning
confidence: 99%